Burden of illness and healthcare resource use in United States patients with sporadic inclusion body myositis. Issue 5 (30th May 2017) - Capkun, Gorana; Callan, Aoife; Tian, Haijun; Wei, Zhongyuan; Zhao, Changgeng; Agashivala, Neetu; Barghout, Victoria
ABSTRACT: Introduction: We analyzed the burden of illness of sporadic inclusion body myositis (sIBM) patients and the costs to the healthcare system. Methods: A retrospective cohort analysis of 333 sIBM patients aged ≥ 50 years was performed using United States (U.S.) claims data. sIBM patients were matched in a 1:5 ratio to randomly selected individuals with ≥1 healthcare encounter within the year of index date. Results: sIBM patients presented with higher rates of disease‐ and muscle‐related conditions, such as myalgia, myositis, muscle weakness, dysphagia, pneumonia, and falls. Use of healthcare resources, including physical therapy, office visits, emergency room (ER) visits, and hospitalizations, was greater in sIBM patients. This was also reflected in significantly higher overall healthcare costs in the sIBM population driven mainly by more all‐cause office visits, all‐cause ER visits and hospitalizations. Conclusions: sIBM imposes a substantial burden on U.S. patients in terms of additional healthcare usage and associated costs. Muscle Nerve 56 : 861–867, 2017